1991
DOI: 10.1063/1.105005
|View full text |Cite
|
Sign up to set email alerts
|

Insitu preparation of superconducting Y1Ba2Cu3O7−δ thin films by on-axis rf magnetron sputtering from a stoichiometric target

Abstract: Superconducting Y1Ba2Cu3O7−δ thin films have been fabricated in situ by on-axis rf reactive magnetron sputtering from a single stoichiometric 1-2-3 target. By using high total sputtering pressures (≳400 mTorr) and low oxygen pressures (≤10 mTorr), negative ion resputtering is almost eliminated and high quality oriented films on (100)MgO are realized with excellent reproducibility. Such films display zero resistance Tc’s as high as 88 K with transition widths ΔTc (90%–10%) of about 2 K, residual resistivity rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is widely accepted that oxygen has to be added to the sputtering gas for the deposition of Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-Ca-2212) thin films [1,2,3,4]. The drawback to using oxygen in the sputtering gas is a pronounced resputtering of the deposited film, as found in Bi-Ca-2212 [5,6] and YBa 2 Cu 3 O 7−δ [7,8,9,10,11] superconducting systems. Oxygen anions derived from the sputtering gas and target material are the source of this resputtering effect [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely accepted that oxygen has to be added to the sputtering gas for the deposition of Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-Ca-2212) thin films [1,2,3,4]. The drawback to using oxygen in the sputtering gas is a pronounced resputtering of the deposited film, as found in Bi-Ca-2212 [5,6] and YBa 2 Cu 3 O 7−δ [7,8,9,10,11] superconducting systems. Oxygen anions derived from the sputtering gas and target material are the source of this resputtering effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the substrate is placed at an angle < 90 o relative to the axis of the cylindrical target. It has been found that the energy of oxygen anions that strike the film is reduced [1,5,6,7,8,9,10,11]. Off-axis sputtering greatly reduces the deposition rate, which is not desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• )], is not deleterious to J c (18). However, the elimination of high-angle grain boundaries in HTS materials has been a difficult challenge to overcome.…”
Section: Processing Of High-temperature Superconductorsmentioning
confidence: 99%
“…Since the discovery of high-T c superconductors, highquality thin films have been prepared on oxide singlecrystal substrates such as MgO and SrTiO 3 [1][2][3][4]. These substrates are not suitable for device applications because they are not available in large sizes at low cost.…”
Section: Introductionmentioning
confidence: 99%